Disaster management: a study on knowledge, attitude and practice of community health nurse - Ahayalimudin, Nurul'Ain; Ismail, Aniza; Mohd Saiboon, Ismail (2013)
Background: Nurses accounted to a greater number of healthcare providers. Therefore, it is crucial for nurses, predominantly community health nurse to be prepared in facing disaster as the catastrophic event occurs without warning. Being prepared will reduce nurses’ fright and anxiety, and simultaneously lessen the impact of disaster towards community. The purpose of this study is to determine knowledge, attitude and practice of community health nurse towards disaster management. Method: This cross-sectional study conducted in one of states in Malaysia. The questionnaire distributed to randomly select 312 registered nurses who work in health clinics from October to November 2011. Results: The response rate of community health nurse is 84.6 per cent (n=264). It shows about 40.9 per cent (n=108) of nurses are having adequate knowledge on disaster, 83.3 per cent (n=220) portray a positive attitude and merely 30.7 per cent (n=81) having an adequate practice. It has been identified an association between attending disaster-related education/training with nurses’ knowledge (p<0.001, χ2=24.000), attitude (p<0.05, χ2=4.177) and practice (p<0.001, χ2=25.558). Nurses who attended disaster-related education/training are more likely to have an adequate knowledge (p<0.001, AOR=3.511, 95% CI=2.097-5.881), portraying positive attitude (p<0.05, AOR=2.042, 95% CI=1.025-4.069) and having an adequate practice (p<0.001, AOR=4.080, 95% CI=2.326-7.156) towards disaster management as compared to those who does not have an opportunity to attend disaster-related education/training. Conclusion: It has been proven statistically that adequacy of knowledge and practice, and portraying positive attitude is driven by attendance to the disaster-related education/training program. Thus, primary health care institutions are required to conduct disaster-related education/training regularly as to give an exposure to nurses for managing disaster adequately.